Plasma Uric Acid Helps Predict Cognitive Impairment in Patients With Amyotrophic Lateral Sclerosis - Tang, Jiahui; Yang, Yuan; Gong, Zhenxiang; Li, Zehui; Huang, Lifang; Ding, Fengfei; Liu, Mao; Zhang, Min (Frontiers in Neurology, 2021)
Objective: Uric acid as an antioxidant plays an important role in neurodegenerative disease. Our objective is to investigate the relationship between plasma uric acid and cognitive impairment in patients with amyotrophic lateral sclerosis (ALS). Methods: In this cross-sectional study, 124 ALS patients were screened by the Edinburgh Cognitive and Behavioral Screen (ECAS) and classified according to the revised Strong's criteria. Additionally, based on total ECAS cut-off score patients were categorized into those with cognitive impairment (ALS-cie) and those without cognitive impairment (ALS-ncie), and clinical data and uric acid level were compared between the two groups. Parameters with significant differences were further included in a multivariate linear regression analysis with ECAS score as a dependent variable. Hold-out validation was performed to evaluate the fitness of regression model. Results: Up to 60% of ALS patients showed cognitive or/and behavioral impairment. The ALS-cie group had lower education level (p < 0.001), older age at symptom onset (p = 0.001), older age at testing (p = 0.001), and lower plasma uric acid (p = 0.01). Multivariate analysis showed increased uric acid (β = 0.214, p = 0.01), lower age at testing (β = −0.378, p < 0.001), and higher education level (β = 0.424, p < 0.001) could predict higher ECAS score (F = 19.104, R2 = 0.381, p < 0.0001). Validation analysis showed that predicted ECAS score was significantly correlated with raw ECAS score in both the training set (rs = 0.621, p < 0.001) and the testing set (rs = 0.666, p < 0.001). Conclusions: Cognitive impairment was a common feature in our Chinese ALS patients. Plasma uric acid might help evaluate the risk of cognitive impairment in ALS patients when combined with education level and age at testing.